2018
DOI: 10.2147/ceor.s178934
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of ribociclib versus palbociclib in the first-line treatment of HR+/HER2– advanced or metastatic breast cancer in Spain

Abstract: PurposeThe aim of this study was to evaluate the cost-effectiveness of ribociclib compared to palbociclib, both in combination with letrozole, in the first-line treatment of postmenopausal women with hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2−) advanced or metastatic breast cancer (ABC) from the perspective of the Spanish National Health System (NHS).Patients and methodsDisease progression was simulated with a partitioned survival model developed from the parameteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 41 publications
(55 reference statements)
1
43
1
Order By: Relevance
“…Our results are comparable with overseas cost‐effectiveness studies which found palbociclib or ribociclib were not cost‐effective in the first‐line setting, with ICERs ranging between USD100,000‐770 000/QALY 9‐13 . We did not compare the cost‐effectiveness of ribociclib with other CDK4/6 inhibitors but several studies have reported that ribociclib is either cost‐saving or cost‐effective compared to palbociclib 12,33 . Of note, as none of the phase 3, first‐line CDK4/6 inhibitor studies have reported mature OS results, all published CEAs were either based on immature OS data or data from, a small phase 2 trial which did not show an OS benefit.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our results are comparable with overseas cost‐effectiveness studies which found palbociclib or ribociclib were not cost‐effective in the first‐line setting, with ICERs ranging between USD100,000‐770 000/QALY 9‐13 . We did not compare the cost‐effectiveness of ribociclib with other CDK4/6 inhibitors but several studies have reported that ribociclib is either cost‐saving or cost‐effective compared to palbociclib 12,33 . Of note, as none of the phase 3, first‐line CDK4/6 inhibitor studies have reported mature OS results, all published CEAs were either based on immature OS data or data from, a small phase 2 trial which did not show an OS benefit.…”
Section: Discussionsupporting
confidence: 57%
“…[9][10][11][12][13] We did not compare the cost-effectiveness of ribociclib with other CDK4/6 inhibitors but several studies have reported that ribociclib is either cost-saving or cost-effective compared to palbociclib. 12,33 Of note, as none of the phase 3, first-line CDK4/6 inhibitor studies have reported mature OS results, all published CEAs were either based on immature OS data or data from, a small phase 2 trial which did not show an OS benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Utilities of 0.715 and 0.443 were used for the PF and PD states, respectively, based on a primary utility study by Lloyd et al 14 The choice of this study was consistent with prior economic analyses. [15][16][17][18] Disutilities due to adverse events (AEs) were not included in the model as the reported differences in incidences of AEs between the two treatment groups were not considered significant enough to result in differences in quality of life.…”
Section: Utilitiesmentioning
confidence: 99%
“…number of LYs) to produce the outcome of QALYs in the model. Utilities of 0.715 and 0.443 were used for the PF and PD states, respectively, based on a primary utility study by Lloyd et al [18] The choice of this study was consistent with prior economic analyses [19][20][21][22]. Disutilities due to adverse events (AEs) were not included in the model as the reported differences in incidences of AEs between the two treatment groups were not considered significant enough to result in differences in quality of life.…”
Section: Utilitiesmentioning
confidence: 99%